2022
DOI: 10.3390/w14172759
|View full text |Cite
|
Sign up to set email alerts
|

Research on Temporal and Spatial Differentiation and Impact Paths of Agricultural Grey Water Footprints in the Yellow River Basin

Abstract: The scientific evaluation of water pollution in the Yellow River Basin was directly related to the sustainable utilization of water resources and the green development of the agricultural economy in this region. In this study, we focused on the planting industry, and measured the agricultural grey water footprint of 73 prefecture-level cities in the Yellow River Basin from 2000 to 2019. We used spatial autocorrelation analysis to reveal temporal and spatial differentiation characteristics, and we used the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Kong et al also found that China's AGWF showed a downward trend from 2015 to 2019 [6]. Xu et al further found that the AGWF of prefecture-level cities in the YRB continued to decline from 2015 to 2019 [50]. The research conclusions of this paper are consistent with those of Kong et al and Xu et al [6,50].…”
Section: Discussion Of Agwfsupporting
confidence: 88%
See 1 more Smart Citation
“…Kong et al also found that China's AGWF showed a downward trend from 2015 to 2019 [6]. Xu et al further found that the AGWF of prefecture-level cities in the YRB continued to decline from 2015 to 2019 [50]. The research conclusions of this paper are consistent with those of Kong et al and Xu et al [6,50].…”
Section: Discussion Of Agwfsupporting
confidence: 88%
“…Xu et al further found that the AGWF of prefecture-level cities in the YRB continued to decline from 2015 to 2019 [50]. The research conclusions of this paper are consistent with those of Kong et al and Xu et al [6,50]. The reason why the AGWF in the YRB decreased at first and then rose slowly during 2016-2021 may be that the implementation of the highquality development strategy in the YRB had a strong promotion effect on reducing the agricultural grey water footprint and improving agricultural water use efficiency in the region in 2016 and for the following three years.…”
Section: Discussion Of Agwfmentioning
confidence: 98%
“…Therefore, we require a method to manage water pollution. In the Yellow River Basin, Xu et al (2022) conducted a study of a similar nature, however they came to two distinct results on the spatial differences in the AGWFs across the cities. (1) There are stark differences in the amount of GWF planted in prefecture-level cities.…”
Section: Resultsmentioning
confidence: 99%
“…Because this study solely looked at the GWF of the planting industry, there are some differences between it and Xu et al (2022) on specific uses of water.…”
Section: Resultsmentioning
confidence: 99%
“…4 show the temporal and spatial distribution patterns of financial technology and bank performance plotted separately before this paper's standard deviation ellipse analysis. The method used is the natural breakpoint method, which is based on Xu et al [ 42 ] and Zhang et al [ 43 ] to classify and analyze the distribution of the two at 2012, 2015, 2018, and 2021 to classify their ranks and analyze their distribution characteristics.
Fig.
…”
Section: Empirical Analysesmentioning
confidence: 99%